Posição socioeconômica no curso de vida e comportamentos de risco relacionados à saúde: ELSA-BRASIL - Jéssica Costa Faleiro (2016)
Non-communicable chronic diseases (NCDs) contribute to the global burden of disease and leading cause of death in the country and the world. These premature deaths are largely preventable by reducing their major modifiable risk factors such as unhealthy diet, physical inactivity, and smoking. It is known that the adoption of these behaviors is dependent on socioeconomic circumstances in which people are born, grow and work, and not just an individual choice. This has been one of the mechanisms explaining the relationship between exposure to socioeconomic adversity and increased morbidity and mortality from NCDs. Besides the importance of socioeconomic position (SEP) in adulthood, socioeconomic circumstances throughout life have been shown to be important for different health outcomes and little is known of their influence in the determination of behavior in adulthood in men and women. The aim of this study was to investigate the association of low SEP across the life course (childhood, youth and adulthood) with low consumption of fruits and vegetables, physical inactivity and smoking in men and women participating in the baseline of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). Additionally, we evaluated whether intra-generational social mobility was associated with health-risk behaviors. Were analyzed baseline data of 13216 civil servants between 35 and 74 years of age participants from ELSA-Brasil (20082010). ELSA-Brasil is a multicenter cohort developed in universities and research institutions in six Brazilian states: Minas Gerais, São Paulo, Rio de Janeiro, Espírito Santo, Bahia e Rio Grande do Sul. The response variables were low fruit and vegetable consumption (< 1/day), physical inactivity (<150 minutes/week of moderate physical activity or <75 minutes/week of strong physical activity) and smoking (never, former smoker, current smoker). SEP indicators were maternal education, youth occupational social class, adulthood occupational social class and social trajectory (youth vs adulthood occupational social class). Binomial and multinomial logistic regressions were used to estimate the independent association between each explanatory and response variables stratified by sex. The prevalence of risk behaviors was higher among men, except physical inactivity. Social disadvantages in adulthood were consistently associated with higher prevalence of low intake of fruit and vegetables in both sexes (men: OR: 2.17; 95%CI: 1.84 -2.57; women: OR: 1.69; 95%CI: 1.40-2.04), physical inactivity (men: OR: 2.25; 95%CI: 1.91-2.66; women: OR: 4.57; 95%CI: 3.23-6.49) and smoking (men: OR: 3.80; 95%CI: 2.85-5.06; women: OR: 2.82; 95%CI: 2.02-3.94). However, the SEP in youth and childhood were associated with behaviors less consistently. For example, while the low maternal education reduced the chance of past smoking in women (OR: 0.66; 95%CI: 0.52-.085) and current smoking in men (OR: 0.58; 95%CI: 0,42-0.81) and women (OR: 0.62; 95%CI: 0.45-0.85), it was associated with a higher chance of physical inactivity among women (OR: 1.59; 95%CI : 1.25-2.03). Low SEP at youth increased the chance of past smoking in men (OR: 1.40; 95%CI: 1.00-1.96) and women (OR: 1.43; 95%CI: 1,03-1.99) and either increased the chance of current smoking in women (OR: 1.72; 95%CI: 1.08-2.75). The social trajectories analysis gave additional support to the greater relevance of the adult life disadvantages to health-risk behavior, as only individuals who have ascended to the high socio-occupational class showed no larger chance of these behaviors compared to participants who always was at high social class. Our results add to evidence that health-risk behaviors express the social circumstances in which individuals live and grow. Indicate a higher prevalence of risk behaviors in men than in women. Socioeconomic adversity in adulthood seems to have a greater influence on the risk behaviors than childhood and youth socioeconomic disadvantages. Childhood social adversity seems more relevant for women health behaviors, but in a contradictory manner, since it is associated with the lower chance of smoking and the greater chance of physical inactivity. Only ascendants to the high class do not have a greater chance of health-risky behaviors, reinforcing the importance of adulthood socioeconomic position relevance to health-risk behaviors. Improve the socioeconomic inequalities can impact on health-related behaviors and consequently the morbidity and mortality from chronic diseases.